Large‐scale inflation of Tungurahua volcano (Ecuador) revealed by Persistent Scatterers SAR interferometry. Issue 16 (20th August 2014) - Champenois, J.; Pinel, V.; Baize, S.; Audin, L.; Jomard, H.; Hooper, A.; Alvarado, A.; Yepes, H.
Abstract The Tungurahua volcano, in Ecuador, has been experiencing a substantial activity period since 1999, with several eruptions, including those of 2006 and 2008. We use a persistent scatterers approach to analyze a time series of Envisat synthetic aperture radar (SAR) data over the period 2003–2009, to investigate surface deformation in the region of the volcano. We measure a continuous large‐scale uplift with a maximum line of sight displacement rate of about 8 mm/yr, which is the first evidence of a sustained inflation in the Andes for an active volcano encompassing several eruptions. We model this signal as magma emplacement in a permanent storage zone at 11.5 km below sea level, with a net inflow rate of 7 million m3/yr. The paroxysmal eruptions in 2006 and 2008 did not seem to disrupt this long‐term signal. However, we observe significant deformation during the 2006 eruption consistent with an additional intrusion of 4.5 million m3 of magma.